Endophytic Bacterial Communities Associated with Roots and Leaves of Plants Growing in Chilean Extreme Environments - Zhang, Qian; Acuna, Jacquelinne J.; Inostroza, Nitza G.; Mora, Maria Luz; Radic Schilling, Sergio Javier; Sadowsky, Michael J.; Jorquera, Milko A. (My University, 2019)
Several studies have demonstrated the relevance of endophytic bacteria on the growth and fitness of agriculturally-relevant plants. To our knowledge, however, little information is available on the composition, diversity, and interaction of endophytic bacterial communities in plants struggling for existence in the extreme environments of Chile, such as the Atacama Desert (AD) and Patagonia (PAT). The main objective of the present study was to analyze and compare the composition of endophytic bacterial communities associated with roots and leaves of representative plants growing in Chilean extreme environments. The plants sampled were: Distichlis spicate and Pluchea absinthioides from the AD, and Gaultheria mucronata and Hieracium pilosella from PAT. The abundance and composition of their endophytic bacterial communities was determined by quantitative PCR and high-throughput sequencing of 16S rRNA, respectively. Results indicated that there was a greater abundance of 16S rRNA genes in plants from PAT (10(13) to 10(14) copies g(-1) DNA), compared with those from AD (10(10) to 10(12) copies g(-1) DNA). In the AD, a greater bacterial diversity, as estimated by Shannon index, was found in P. absinthioides, compared with D. spicata. In both ecosystems, the greater relative abundances of endophytes were mainly attributed to members of the phyla Proteobacteria (14% to 68%), Firmicutes (26% to 41%), Actinobacteria (6 to 23%) and Bacteroidetes (1% to 21%). Our observations revealed that most of operational taxonomic units (OTUs) were not shared between tissue samples of different plant species in both locations, suggesting the effect of the plant genotype (species) on the bacterial endophyte communities in Chilean extreme environments, where Bacillaceae and Enterobacteriacea could serve as keystone taxa as revealed our linear discriminant analysis.
Keywords: None